1997
DOI: 10.1046/j.1365-2036.1997.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole 30 mg daily versus ranitidine 150 mg b.d. in the treatment of acid‐related dyspepsia in general practice

Abstract: Aim: To compare lansoprazole 30 mg daily with ranitidine 150 mg b.d. in the treatment of acid‐related dyspepsia in general practice. Methods: In a double‐blind, parallel group, randomized, multicentre study conducted in 32 general practices in the UK, 213 patients were randomized to receive lansoprazole 30 mg daily, and 219 to receive ranitidine 150 mg b.d., for 4 weeks. All patients had experienced symptoms of reflux‐like or ulcer‐like dyspepsia on at least 4 of the 7 days prior to the study; 75% had experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 8 publications
3
66
1
2
Order By: Relevance
“…After 2 wk 55% of the lansoprazole patients and 33% of the ranitidine group were symptom-free (P = 0.001) with corresponding 4-wk figures of 69% and 44%, respectively (P = 0.001). In the lansoprazole group, at 4 wk, 80% of patients were free of daytime heartburn and 81% of night-time epigastric pain, compared with 55% (P = 0.001) and 65% (P = 0.01) in the ranitidine group [25] . Peura et al [26] compared the efficacy of lansoprazole with placebo in relieving upper abdominal discomfort in 921 patients with functional dyspepsia in a blinded-randomized trial and moderate upper abdominal discomfort on at least 30% of screening days [26] .…”
Section: Proton Pump Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…After 2 wk 55% of the lansoprazole patients and 33% of the ranitidine group were symptom-free (P = 0.001) with corresponding 4-wk figures of 69% and 44%, respectively (P = 0.001). In the lansoprazole group, at 4 wk, 80% of patients were free of daytime heartburn and 81% of night-time epigastric pain, compared with 55% (P = 0.001) and 65% (P = 0.01) in the ranitidine group [25] . Peura et al [26] compared the efficacy of lansoprazole with placebo in relieving upper abdominal discomfort in 921 patients with functional dyspepsia in a blinded-randomized trial and moderate upper abdominal discomfort on at least 30% of screening days [26] .…”
Section: Proton Pump Inhibitorsmentioning
confidence: 99%
“…Responders had fewer clinic visits than non-responders (1.5 vs 2.0 mean visits) and fewer days on medication (mean, 9 d vs 23 d) over the 3-mo period (both, P < 0.001). The quality of life in responders was better at study entry and persisted over 3 mo (all, P < 0.001) Two large studies using lansoprazole have been published [25][26] . Jones et al performed a double-blind, parallel group, randomized, multi-center study in 32 general practices in the UK [25] .…”
Section: Proton Pump Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…All seven trials were RCTs, but only five 142,144,[146][147][148] reported their method of allocation, and only three of these 144,146,147 the mechanism of sequence generation. One study used a centralised telephone randomisation service.…”
Section: Randomisation and Concealment Of Allocationmentioning
confidence: 99%